Semiparametric estimation of quantile treatment effects with endogeneity - Kaspar Wüthrich (University of Bern, Department of Economics, 2015)
This paper studies estimation of conditional and unconditional quantile treatment effects based on the instrumental variable quantile regression (IVQR) model (Chernozhukov and Hansen, 2004, 2005, 2006). I introduce a class of semiparametric plug-in estimators based on closed form solutions derived from the IVQR moment conditions. These estimators do not rely on separability of the structural quantile function, while retaining computational tractability and root-n-consistency. Functional central limit theorems and bootstrap validity results for the estimators of the quantile treatment effects and other functionals are provided. I apply my method to reanalyze the effect of 401(k) plans on individual savings behavior.
Keywords: C14; C21; C26; 330; instrumental variables; quantile treatment effects; distribution regression; functional central limit theorem; Hadamard differentiability; exchangeable bootstrap